Who Has Active Lifestyles? Sociodemographic and Personality Correlates of Activity Diversity in Two Samples of Adults. (13th December 2022) - Lee, Soomi; Ng, Yee To; Charles, Susan T; Almeida, David M; Fingerman, Karen L
Abstract: Objectives: Activity diversity—an index of active lifestyles that captures variety (number) and evenness (consistency) in activity engagement—is known to support health in adulthood. However, less is known who has higher or lower activity diversity, information that helps identify individuals who may be at greater risk for poor health. This article examined sociodemographic characteristics and Big Five personality traits that may be associated with activity diversity. Methods: We used 2 independent project samples ( n sample1 = 2, 699; n sample2 = 301). Sample 1 included U.S. national adults in a wide age range (25–84). Sample 2 included U.S. community-dwelling older adults (age = 65–89). Each study asked about different types of activity engagement using surveys. The activity diversity index was calculated in each sample, using Shannon's entropy method. Results: In Sample 1, older adults, women, non-Hispanic White individuals, married/partnered individuals, and those with higher education and fewer functional limitations had higher activity diversity. Additionally, higher conscientiousness, higher extraversion, and lower neuroticism were each associated with higher activity diversity after controlling for sociodemographic factors. Extraversion and neuroticism remained significant in the younger group (age < 65) of Sample 1, but only extraversion was a significant factor associated with activity diversity in the older group (age ≥ 65). The results in the older group were generally replicated in Sample 2, such that higher extraversion in older adults was consistently associated with higher activity diversity independent of the strong correlates of sex, education, and functional limitations. Discussion: Findings were discussed in terms of age-specific associations between sociodemographic and personality characteristics and activity diversity.